INFLUENCE OF SUBJECTIVE EXERCISE EXPERIENCE ON RECREATIONAL EXERCISING - Dražen Čular; Frane Žuvela; Ivana K. Lujan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Effects of physical activity on psychological health and well-being have been intrigued topic for many researches (McAuley & Courneya, 1994). Also, the positive subjective experience lies in the basis of every successful recreational activity and training. However, the influence of different types of activities and their gender specifics regarding self-reported well-being have not yet been investigated. The aims of this study were: (1) to analyse gender differences before and after physical activity in "Subjective Exercise Experience Scale"(SEES) in group of subjects involved in aesthetic and non-aesthetic recreational physical activities and (2) to determine differences between subjects involved in aesthetic and non-aesthetic recreational physical activities before and after the activity for female and male group separately. The SEES was used to assess psychological responses to exercise among female (N=32) and male (N=83) recreational athletes. The 12 items of SEES represented three-aspects of exercise experience: Positive Well-Being, Psychological Distress and Fatigue. The results showed significant gender differences only in non-aesthetic group before and after physical activity in Psychological Distress subscale. Female students (Mean=4.8) had lower values of Psychological Distress than Male students (Mean=6.9). Furthermore, female aesthetic group (Mean=24.4) had significantly higher values in Positive Well-Being subscale after physical activity than female nonaesthetic group (Mean=18.8), while male aesthetic group had significantly higher values in Positive Well-Being subscale before and after physical activity than male non-aesthetic group. It is possible to conclude that aesthetic activities have positive effect on both female and male sample. It is possible that music increased emotionally experienced activity and contributed to better physical well being especially among female recreational athletes.